2021
DOI: 10.1002/mds.28487
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Spectrum of AP5Z1‐Related Hereditary Spastic Paraplegia (HSP‐SPG48): A Multicenter Study on a Rare Disease

Abstract: Relevant conflicts of interest/financial disclosures: M.B. has received a research grant from the European Academy of Neurology (EAN) and travel grants from Merck, Teva, Genesis Pharma, Pfizer, and Novartis. G.K. has received research grants from Genesis Pharma and Teva and consultation fees, advisory boards, and honoraria from Genzyme, Genesis Pharma, Teva, and Novartis. J.T. has shares in a diagnostic laboratory (Tzartos Neurodiagnostics) in Athens. All other authors report no disclosures relevant to the man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Among forms affecting directly the autophagy and lysosomal pathways, miglustat was succefully used to reduce ganglioside accumulation in SPG11 zebrafish models (Boutry et al, 2018), and tideglusib, a GSK3b inhibitor, prevented the neurite pathology in brain organoids of SPG11 patients (Pozner et al, 2018). Autophagy regulators might also be of interest in SPG48 (Breza et al, 2021) and rapamycin partially reversed the phenotype induced by Atlastin-1 loss of function in flies (Xu et al, 2017). In zebrafish mimicking SPG3, the modulation of the BMP pathway was also of interest to rescue the motor phenotype (Fassier et al, 2010).…”
Section: Therapeutic Options and Opportunitiesmentioning
confidence: 99%
“…Among forms affecting directly the autophagy and lysosomal pathways, miglustat was succefully used to reduce ganglioside accumulation in SPG11 zebrafish models (Boutry et al, 2018), and tideglusib, a GSK3b inhibitor, prevented the neurite pathology in brain organoids of SPG11 patients (Pozner et al, 2018). Autophagy regulators might also be of interest in SPG48 (Breza et al, 2021) and rapamycin partially reversed the phenotype induced by Atlastin-1 loss of function in flies (Xu et al, 2017). In zebrafish mimicking SPG3, the modulation of the BMP pathway was also of interest to rescue the motor phenotype (Fassier et al, 2010).…”
Section: Therapeutic Options and Opportunitiesmentioning
confidence: 99%
“…In most patients, brain MRI shows white matter lesions around corona radiata, semioval center and lateral ventricles. The “ears of the lynx” imaging sign suggests the presence of a genetic mutation, likely characteristic of HSP ( 12 ). The narrowing of corpus callosum is another relevant imaging characteristic in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to an extended analysis of all SPG48 patients by Breza et al (2021), 21 AP5Z1 variants (SPG48) from 18 families have been identified in the literature. 7 Some examples include Slabicki et al (2010) who identified a homozygous truncating mutation in 2 affected French sibs (613653.0001). Another patient with sporadic disease was heterozygous for another truncating mutation (613653.0002).…”
Section: Discussionmentioning
confidence: 99%